O trabalho das mulheres camponesas e a desigualdade de gênero nos faxinais marmeleiro de baixo e linha Paraná Anta Gorda, nos municípios de Rebouças e Prudentópolis/PR - Franco, Renata Brasileiro (2019)
The present research seeks to understand the work and gender inequalities among the of the peasant women faxinalenses, identifying the activities performed by them in productive and reproductive labor, as well as their participation and organization of resistance and fight in the field. To answer the objectives, bibliographical, documentary and field investigations were carried out. In this sense, a case study of Quali-quantitative character was carried out, being descriptive-interpretative, which took as a sample the faxinais of Marmeleiro de Baixo, in Rebouças, PR and Linha Paraná Anta Gorda, in Prudentópolis, PR. The research was divided into three chapters: the first deals on peasantry from the resistance in the faxinais; The second is a discussion about gender and sexual division of labor in the field, as well as the movement of fight and resistance of peasant women; And the third, discusses the performance of women faxinalenses in productive and reproductive labor and their visibility and valorization, as well as the participation and organization of these women. To this end, the empirical data collection was made from structured interviews and participant observation, in the respective faxinais, as well as in meetings of the APF and at the 7th State Meeting of the Faxinalenses. Thus, it was possible to understand how the sexual division of labor in the productive units is given, in which the reproductive labor falls under the responsibility, almost integral, of the women faxinalense. The productive labor is subdivided into: outside the house, this being the agricultural activities, in which women perform, together with their husbands and daughters; and the productive labor in the scope of the house, which is related to the commercialization of the artisan production, the products of the vegetable garden and animals, remembering that these, are carried out care practices that, most of them, are the responsibility of women. This entails the execution of the double and/or triple working hours of women. In addition to the work, women participate and organize themselves in social movements or groups of women to resist and fight against the reproduction of practices of oppression and domination.